PD-L1 expression on circulating tumor cells and platelets in patients with metastatic breast cancer. - Elizabeth P Darga (Public Library of Science (PLoS), 2021)
Background Immune checkpoint inhibition is effective in several cancers. Expression of programmed death-ligand 1 (PD-L1) on circulating tumor or immune effector cells could provide insights into selection of patients for immune checkpoint inhibition. Methods Whole blood was collected at serial timepoints from metastatic breast cancer patients and healthy donors for circulating tumor cell (CTC) and platelet PD-L1 analysis with a phycoerythrin-labeled anti-human PD-L1 monoclonal antibody (Biolegend clone 29E.2A3) using the CellSearch® assay. CTC PD-L1 was considered positive if detected on at least 1% of the cells; platelet PD-L1 was considered positive if ≥100 platelets per CellSearch frame expressed PD-L1. Results A total of 207 specimens from 124 metastatic breast cancer patients were collected. 52/124 (42%) samples at timepoint-1 (at or close to time of progressive disease) had ≥5 CTC/7.5ml whole blood. Of those, 21 (40%) had positive CTC PD-L1. In addition, platelet PD-L1 expression was observed in 35/124 (28%) at timepoint-1. Platelet PD-L1 was not detected in more than 70 specimens from 12 healthy donors. Platelet PD-L1 was associated with ≥5 CTC/7.5ml whole blood (p = 0.0002), less likely in patients with higher red blood cell counts (OR = 0.72, p<0.001) and a history of smoking tobacco (OR = 0.76, p<0.001). Platelet PD-L1 staining was not associated with tumor marker status, recent procedures or treatments, platelet-affecting drugs, or CTC PD-L1 expression. Conclusion PD-L1 expression was found in metastatic breast cancer patients on both CTC and platelets in an independent fashion. Inter-patient platelet PD-L1 expression was highly heterogeneous suggesting that it is a biological event associated with cancer in some but not all patients. Taken together, our data suggest that CTC and platelet PD-L1 expression could play a role in predicting which patients should receive immune checkpoint inhibition and as a pharmacodynamics biomarker during treatment.